IDDF2018-ABS-0038 Outcome of per oral endoscopic myotomy in children with achalasia with a median follow -up of 540 days. (June 2018) - Nabi, Zaheer; Chavan, Radhika; Ramchandani, Mohan; Shava, Upender; Nageshwar Reddy, D
Abstract : Background: Achalasia cardia (AC) is rare in children, and optimum endoscopic management options are not well known. Per oral endoscopic myotomy (POEM) is a novel treatment modality for AC with excellent results in adult patients. However, the long-term outcomes of POEM are not known in children. In this study, we aim to evaluate the outcome of POEM in AC. Methods: We analysed the data of all the children (£18 years) with AC who presented to our hospital from September 2013 to January 2018. The outcomes of POEM that were assessed included – technical success, clinical success and adverse events. Post-POEM, gastroesophageal reflux (GERD) was assessed with 24 hour pH-impedance, and esophagogastroduodenoscopy (EGD). Results: A total of 43 children (boys-22, girls-21) with mean age, 14.5±3.41 years (4–18) with AC underwent POEM during the study period. The subtypes of achalasia according to Chicago classification were – type I- 11, type II- 29, III- 2 and unclassified-1. Eighteen children (41.9%) had a history of prior treatment including – pneumatic dilatation (15), laparoscopic Heller's myotomy (1) and both dilatation and Heller's myotomy (2). POEM was successfully performed in all the children (technical success-100%). Intra-operative adverse events occurred in 11 (25.6%) children including retroperitoneal CO2 (7), capnoperitoneum (3) and mucosal injury (1). At a median follow-up of 540 days (66–1594), the clinical success was 95.3% (39/41). Clinical success was 92.8% (26/28), 94.4% (17/18), 92.3% (12/13), 83.3% (5/6) at 1, 2, 3, and 4 years follow-up respectively. GERD was assessed in 20 children. Erosive esophagitis was detected in 55% (11/20). On 24 hour pH study, high De-Meester score was detected in 53.8% (7/13) children. Conclusions: POEM is safe and effective for the management of achalasia in children. However, GERD is a potential concern and therefore, randomised comparison with Heller's myotomy combined with fundoplication is warranted in future trials.